Pengaruh Filsafat Administrasi Pendidikan The Influence of the Philosopy of Educational Administration - Fitri, Susanti Arian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Education is an important thing in human life. Every individual develops well through education. Education makes many contributions for every individual in developing their humanity. The achievement of the lofty goals of education may be hampered if the implementation of education is not managed professionally. Apart from that, education may be held far from the spirit of truth and applicable ethical norms. In this context, the role of administrative philosophy is needed to direct the parties involved in the implementation of education to explore and discover the deepest goals of education. Since the proclamation, the Indonesian nation has had the Pancasila philosophy which is the basis of the state as well as the basis of national education. Pancasila has been used as a guideline in making national education policies in general and in renewing the content of education in particular. This means that the direction of planning, policy and implementation of education should lead to the goals as outlined by the 1945 Constitution and Pancasila as the basis of national education.